All the grand dukes' men: an overview of the Persian information network of Medici Tuscany between 1600 and 1639. - Trentacoste, Davide (Mediterranean Historical Review, 2023)
This article provides an overview of the Tuscan information network on Safavid Persia, paying particular attention to the first decades of the seventeenth century. Since Tuscany established diplomatic relations with Persia in an anti-Ottoman spirit, the issue of how the grand dukes were able to obtain information on Persia was also of primary importance. This was because important strategic and diplomatic decisions in the eastern Mediterranean could also depend on the situation in Persia, particularly the military one. Through the analysis of largely unpublished documentation, this article aims to clarify, at least in part, the functioning of the information network concerning Persia, as part of the Tuscan Eastern network, especially focusing on the issue of informers. This will also provide some insights into the evolution of the Persian (and Levantine) information network of Medici Tuscany and on (almost) all the grand dukes' men involved in it.